Quantifying Inner Source Software Development for Business Process Usage - Buchner, Stefan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2024)
Inner source refers to the application of open source development principles within corporate environments. Essentially, it involves embracing open collaboration and contribution without necessarily developing open source software. One fundamental concept borrowed from open source development is the practice of opening software projects to external contributions. In the realm of inner source, these contributions usually originate from developers engaged in other projects or working in different organizational units. This collaborative approach yields mutual benefits through joint software development. However, these inner source contributions often cross organizational and legal boundaries, significantly impacting a wide range of business processes. These effects extend beyond software development and affect strategic and operational functions across various departments, including management, accounting, and even taxation. Currently, these processes are not harmonized with the inner source way of intellectual property flow within the company. This misalignment can lead to mismanagement and even profit shifting. The primary objective of this dissertation is to address these challenges by making three consecutive contributions: First, we conducted a systematic literature review, combined with thematic analysis, to assess the current state of inner source measurement and its impact on various business processes. This qualitative data analysis categorizes a range of approaches and evaluates their suitability for application within the inner source domain. Second, building on the insights derived from our systematic literature review, we developed an inner source research model. This model serves as a foundation, providing researchers with a unified framework for advancing toward more precise and comprehensive inner source measurement. It, in turn, enables the development of future tools and techniques and facilitates the creation of metrics tailored to inner source management, aligning existing business processes with the inner source paradigm. Third, we have implemented a first algorithm for the financial assessment of inner source contributions. This algorithm estimates the time invested in code contributions by individual contributors or departments. These estimations, in turn, enable cost calculations that can be applied to business processes affected by inner source, such as tax contribution assessments. Lastly, we consolidate individual contributions, clarify thematic connections, integrate outside research, and explore future prospects. In summary, this dissertation lays the theoretical groundwork for the financial evaluation of inner source contributions. It offers guidance to researchers on conducting measurement-related inner source research and provides practitioners with insights into the development of inner source metrics and tools. Furthermore, this dissertation introduces an initial algorithm, practically evaluated for its usability in conducting cost calculations within the inner source doma